2013
DOI: 10.1186/1468-6708-14-124
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center study on the regenerative effects of erythropoietin in burn and scalding injuries: study protocol for a randomized controlled trial

Abstract: Background: Although it was initially assumed that erythropoietin (EPO) was a hormone that only affected erythropoiesis, it has now been proposed that EPO plays an additional key role in the regulation of acute and chronic tissue damage. Via the inhibition of inflammatory reactions and of apoptosis, stem cell recruitment, advancement of angiogenesis and growth factor release, EPO enhances healing and thus restitutio ad integrum after trauma. Human skin contains EPO receptors and is able to synthesize EPO. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…EPO can protect epidermis, dermis, and its vital structures, in particular capillaries and blood vessels, from further damage following burn injury [28]. In fact, it has been demonstrated that erythropoietin may also act on nonhaematopoietic tissues via the EPOR, stimulating tissue healing, particularly following injury [29, 30].…”
Section: Resultsmentioning
confidence: 99%
“…EPO can protect epidermis, dermis, and its vital structures, in particular capillaries and blood vessels, from further damage following burn injury [28]. In fact, it has been demonstrated that erythropoietin may also act on nonhaematopoietic tissues via the EPOR, stimulating tissue healing, particularly following injury [29, 30].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of tissue-protective molecules, including EPO, CEPO and pHBSP, in various models of wound healing such as burn injury (34) and cutaneous punch wound (27,35), A case report on the effect of EPO on the healing of skin ulcers was reported (36) and a multicenter clinical trial is ongoing with EPO in burn and scald injuries (37). Whilst the possible wound healing actions of EPO have been investigated in other contexts, most of these studies have focused on skin wounds and their inflammatory and microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…These promising clinical results in patients with skin wounds of dissimilar etiologies have encouraged others to initiate clinical investigations whose aim is to assess EPO's action in different wound types. For example, Gunter et al . announced the initiation of a prospective, randomized, double‐blind, multicenter study in 150 patients with burn and scald injuries in order to investigate the effect of systemic 150 IU/kg body weight EPO treatment for 21 days.…”
Section: Epo and Wound Healing: Clinical Findingsmentioning
confidence: 99%
“…Therefore, clinical trials whose aim is to assess the safety and efficacy of EPO as potential treatment for wound healing especially in patients with DM are needed. Such a clinical trial whose aim is to assess the efficacy of systemic administered EPO in 150 patients suffering of burn and scalding injuries was announced by Gunter et al . in 2013.…”
Section: Clinical Considerationsmentioning
confidence: 99%